A Comparative Study of National Infrastructures for Digital (Open) Educational Resources in Higher Education - Marin, Victoria I.; Bond, Melissa; Zawacki-Richter, Olaf; Aydin, Cengiz H.; Bedenlier, Svenja; Bozkurt, Aras; Conrad, Dianne; Jung, Insung; Kondakci, Yasar; Prinsloo, Paul; Qayyum, Adnan; Roberts, Jennifer; et al. (Open Praxis, 2020)
This paper reports on the first stage of an international comparative study for the project "Digital educational architectures: Open learning resources in distributed learning infrastructures-EduArc", funded by the German Federal Ministry of Education and Research. This study reviews the situation of digital educational resources (or (O)ER) framed within the digital transformation of ten different Higher Education (HE) systems (Australia, Canada, China, Germany, Japan, South Africa, South Korea, Spain, Turkey and the United States). Following a comparative case study approach, we investigated issues related to the existence of policies, quality assurance mechanisms and measures for the promotion of change in supporting infrastructure development for (O)ER at the national level in HE in the different countries. The results of this mainly documentary research highlight differences and similarities, which are largely due to variations in these countries' political structure organisation. The discussion and conclusion point at the importance of understanding each country's context and culture, in order to understand the differences between them, as well as the challenges they face.
CRIS-Team WoS Importer:2020-09-18

Akademische Mediennutzung Studierender im Corona-Semester 2020 - Bedenlier, Svenja; Händel, Marion; Kammerl, Rudolf; Gläser-Zikuda, Michaela; Kopp, Bärbel; Ziegler, Albert (MedienPädagogik, 2021)
Unter dem Eindruck der CoViD-19 Pandemie erfolgte im Sommersemester 2020 an deutschen Hochschulen flächendeckende Online-Lehre im Notbetrieb. Die vorliegende längsschnittliche Fragebogenstudie untersucht die akademische Mediennutzung, -kompetenz und -ausstattung Studierender (N = 2.037) an einer deutschen Volluniversität zu Beginn und zur Mitte des betreffenden Semesters. Die Ergebnisse zeigen, dass die akademische Mediennutzung intensiviert wird, wahrgenommene digitale Kompetenzen der Studierenden zunehmen und E-Learning Angebote fakultätsspezifisch eingesetzt und genutzt werden. Sichtbar wird jedoch auch, dass Studierende mit heterogenen Voraussetzungen in das Semester starteten, die sich auch im Semesterverlauf auf die Studiensituation auswirkten. Die Ergebnisse werden vor dem Hintergrund bildungspolitischer Bestrebungen hinsichtlich der Digitalisierung der Hochschullehre, mediendidaktischer Fragestellungen und studentischem Eigensinn der Mediennutzung eingeordnet und diskutiert.
Keywords: Emergency Remote Teaching (ERT); Mediennutzung; Studierende; Hochschule

,Bildung’ und ,Digitalisierung’ im Spiegel von Digitalisierungsstrategien - Bedenlier, Svenja; Deimann, Markus (Zeitschrift für Hochschulentwicklung, 2020)
Digitalisierung nimmt im Kontext hochschulischer Bildungsprozesse eine zunehmend zentrale Rolle ein und dies sowohl in der eigentlichen Lehrpraxis als auch in bildungspolitischen Strategien. Um herauszuarbeiten, in welchem Verhältnis die beiden Komplexe Bildung und Digitalisierung zueinander stehen, werden mittels einer qualitativen Inhaltsanalyse die Digitalisierungsstrategien von zwölf Bundesländern untersucht. Die Ergebnisse zeigen, dass beide Komplexe anhand der Aspekte Qualität und Effizienz zusammengedacht werden, aber gleichzeitig der Einsatz digitaler Werkzeuge und Settings dem Bildungsgedanken untergeordnet is
Keywords: Digitalisierungstrategien; Bildungsbegriff; Digitalisierung in der Lehre

Book Review: Culture and Online Learning. Global Perspectives and Research - Bedenlier, Svenja (2016)

Book review: The battle for open: how openness won and why it doesn’t feel like victory - Bedenlier, Svenja (2015)

Correction to: Emergency remote teaching in higher education: mapping the first global online semester (International Journal of Educational Technology in Higher Education, (2021), 18, 1, (50), 10.1186/s41239-021-00282-x) - Bond, Melissa; Bedenlier, Svenja; Marin, Victoria I.; Händel, Marion (International Journal of Educational Technology in Higher Education, 2021)
Following publication of the original article (Bond et al., 2021), it was reported that due to a typesetting error Figs. 1–4 in the HTML version of the article were incorrect. The figures were correct in the PDF version of the published article. The article has been corrected so that the figures in the HTML version of the article match those in the PDF.
CRIS-Team Scopus Importer:2021-10-01

Designing effective synchronous online learning - Gegenfurtner, Andreas; Bedenlier, Svenja; Ebner, Christian; Keskin, Özün; Händel, Marion (Designing Effective Digital Learning Environments, 2024)
Synchronous online learning is situated in synchronous webinars, virtual classrooms, and videoconferences, in which students and teachers communicate live over the Internet across distant geographical locations. Shared virtual platforms with voice-over-IP technology and webcams are used to interact ubiquitously and synchronously in real-time. During the COVID-19 pandemic, the use of synchronous online learning environments in primary, secondary, higher, and continuous education has grown massively. In this chapter, we aim to identify design recommendations that help increase the effectiveness of synchronous online learning. First, we provide an overview of recent meta-analyses on the effectiveness of synchronous online learning compared to synchronous face-to-face and asynchronous online learning. Second, we use this empirical evidence to develop design principles that can guide teachers, trainers, and educators in designing effective synchronous online learning environments. Third, we discuss a research agenda for future studies on synchronous online learning, webinars, and videoconferences in education, and we reflect on some practical affordances, including the use of webcams and breakout rooms.
CRIS-Team Scopus Importer:2025-04-01

Digitalisierung hochschulischer Lehre und der third space: Hochschulprofessionelle als WegbereiterInnen für seamless learning? - Bedenlier, Svenja; Schmidt, Claudia (Seamless Learning – lebenslanges, durchgängiges Lernen ermöglichen. Medien in der Wissenschaft, Band 77. Waxmann. Münster, New York., 2020)

Digitalität, Ethik und Bildung. Ein Narratives Review zu Systematisierung eines internationalen Forschungsfeldes - Kramer, Michaela; Bedenlier, Svenja; Kammerl, Rudolf (MedienPädagogik, 2023)

Digital readiness and its effects on higher education students’ socio-emotional perceptions in the context of the COVID-19 pandemic - Händel, Marion; Stephan, Melanie; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Ziegler, Albert (Journal of Research on Technology in Education, 2020)
The current study investigated how ready higher education students were for emergency remote teaching due to the COVID-19 pandemic and how this influenced their socio-emotional perceptions. Results of N = 1,826 higher education students indicate that they seem to be ready for digital learning. A k-means cluster analysis revealed two groups of students that significantly differed with respect to their readiness for digital learning (in terms of technology equipment availability, prior experiences with e-learning, and skills for digital learning). Finally, students’ socio-emotional perceptions, that is, stress-related emotions (worries, tension, joy, and overload) as well as social and emotional loneliness significantly differed due to cluster membership. Hence, the study points a need for support of higher education students in successfully coping with the challenges of emergency remote studying.

Digital readiness and its effects on higher education students’ socio-emotional perceptions in the context of the COVID-19 pandemic - Händel, Marion; Stephan, Melanie; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Ziegler, Albert (Journal of Research on Technology in Education, 2022)

Digital transformation in German higher education: student and teacher perceptions and usage of digital media - Bond, Melissa; Marín, Victoria; Dolch, Carina; Bedenlier, Svenja; Zawacki-Richter, Olaf (International Journal of Educational Technology in Higher Education, 2018)
Digitalization in Higher Education (HE) institutions is an issue that concerns many educational stakeholders. ICT skills are becoming increasingly relevant in every context, especially in the workplace, therefore one of the prime objectives for universities has become preparing future professionals to be able to deal with problems and search for solutions, including digital competence as a vital skill set. Different policies, initiatives and strategies are currently being proposed in Germany, addressing educational technology innovations in HE. The University of Oldenburg is presented as an example, in an endeavour to gain an understanding of what is being proposed and what is actually happening in teaching and learning in German university classrooms. Two datasets were examined regarding the use and perceptions of students (n = 200) and teachers (n = 381) on the use of digital tools. Findings reveal that both teachers and students use a limited number of digital technology for predominantly assimilative tasks, with the Learning Management System being perceived as the most useful tool. In order to support the broader use of educational technology for teaching and learning purposes, strategies for HE institutions are suggeste
Keywords: University professors; University students; Student perceptions; Teacher perceptions; Digital media usage; Educational technology; Digitalization; Higher education; Germany

Do higher education students have the means to learn during the Covid-19 pandemic? Student demands for distance learning in a suddenly digital landscape - Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Journal for Educational Research Online, 2022)
Across the globe, 2020 terms began under conditions incited by the corona pandemic. Within a relatively short amount of time, universities started to develop and implement online courses for distance learning. These changes in learning and teaching may well have been a challenge for students.The current study is about an online survey at a German full-scale university investigating the unique circumstances under which students began the digital 2020 summer term. Of approximately 38,500 students, N = 5,563 students from across all institutional faculties took part in the survey. Results indicate how well students are equipped with devices for digital learning; what kind of experiences they have already made with online learning; and how competent they reported feeling regarding digital learning. Moreover, group differences between faculties, degrees, and gender were investigated. The study provides important insights into digital higher education during the exceptional pandemic situation. The results are intended to feed into student counselling systems via support by way of access to devices or courses regarding digital key competences, or through counselling for students with special social burden
Keywords: higher education; E-Learning; ICT skills; corona pandemic

Do Higher Education Students Have the Means to Learn During the COVID-19 Pandemic? Student Demands for Distance Learning in a Suddenly Digital Landscape - Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Journal for Educational Research Online, 2022)
Across the globe, 2020 terms began under conditions incited by the corona pandemic. Within a relatively short amount of time, universities started to develop and implement online courses for distance learning. The current study is about an online survey at a German university investigating the unique circumstances under which students began the digital 2020 summer term. Of approximately 38 500 students, N = 5563 students from across all institutional faculties took part in the survey. Results indicate how well students are equipped with devices for digital learning, what kind of experiences they have already made with online learning, and how competent they reported feeling regarding digital learning. The study provides important insights into digital higher education during the exceptional pandemic situation. The results are intended to feed into student counselling systems via support by way of access to devices or courses regarding digital skills, or through counselling for students with special social burdens.
CRIS-Team WoS Importer:2022-07-22

Elements of Open Education: An Invitation to Future Research - Zawacki-Richter, Olaf; Conrad, Dianne; Bozkurt, Aras; Aydin, Cengiz Hakan; Bedenlier, Svenja; Jung, Insung; Stöter, Joachim; Veletsianos, George; Blaschke, Lisa Marie; Bond, Melissa; Broens, Andrea; Bruhn, Elisa; et al. (International Review of Research in Open and Distance Learning, 2020)
This paper explores elements of open education within the context of higher education. After an introduction to the origins of open education and its theoretical foundations, the topics of open and distance learning, international education issues in open education, open educational practices and scholarship, open educational resources, MOOCs, prior learning accreditation and recognition, and learner characteristics are considered, following the framework of macro, meso, and micro levels of research in open and distance learning. Implications for future research at the macro, meso, and micro levels are then provided.<br

Emergency remote teaching in higher education: mapping the first global online semester - Bond, Melissa; Bedenlier, Svenja; Marin, Victoria; Händel, Marion (International Journal of Educational Technology in Higher Education, 2021)
Due to the Covid-19 pandemic that spread globally in 2020, higher education courses were subsequently offered in fully remote, online formats. A plethora of primary studies began investigating a range of topics exploring teaching and learning in higher education, particularly during the initial semester. In order to provide an overview and initial understanding of this emerging research field, a systematic mapping review was conducted that collates and describes the characteristics of 282 primary empirical studies. Findings reveal that research was carried out mostly descriptively and cross-sectionally, focusing predominantly on undergraduate students and their perceptions of teaching and learning during the pandemic. Studies originate from a broad range of countries, are overwhelmingly published open access, and largely focused on the fields of Health & Welfare and Natural Sciences, Mathematics & Statistics. Educational technology used for emergency remote teaching are most often synchronous collaborative tools, used in combination with text-based tools. The findings are discussed against pre-pandemic research on educational technology use in higher education teaching and learning, and perspectives for further research are provided.<br
CRIS-Team Scopus Importer:2021-09-10
Keywords: Covid-19; Educational technology; Emergency remote teaching; Higher education; Systematic mapping review

Engaging students through virtual mobility: A systematic mapping review - Bedenlier, Svenja; Marin, Victoria I. (Digital Experiences of International Students: Challenging Assumptions and Rethinking Engagement., 2020)

Evidence syntheses in educational technology research: What is not published in English is not visible? A tertiary mapping review - Bedenlier, Svenja; Buntins, Katja; Bond, Melissa; Händel, Marion; Marín, Victoria I. (Review of Education, 2025)
Evidence syntheses, such as systematic reviews, aim to summarise the current state of research in a field, often using the publication language of a study as a criterion for inclusion or exclusion. However, this has serious implications for capturing evidence from a wider range of geographical areas, and the potential for linguistic bias. In order to explore this issue, a trilingual tertiary mapping review of 446 evidence syntheses within the field of educational technology (EdTech) and published in English, Spanish and German was undertaken, analysing the frequency of multi- and monolingual evidence syntheses, reasons for language choice by research teams, and the composition of research teams in multi- and monolingual evidence syntheses. Items were included if they were a form of evidence synthesis with an explicit method section, indexed within ERIC, Scopus, Web of Science, Dialnet, FIS-Bildung, or Google Scholar, education-related, and published between 1983 and May 2022. The results showed that only eight languages were considered in published syntheses, only five languages were used to construct search strings, most evidence syntheses included research published in English without explaining why, and multilingual research team composition did not predict multilingual evidence syntheses. The findings suggest the need to address publication languages not only as a formal criterion but as an integral aspect of methodological approach, influencing the content and scope of syntheses in educational research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: educational technology; linguistic bias; meta review; publication language; research methods; research synthesis; review of reviews; systematic review

Facilitating student engagement through educational technology in higher education: A systematic review in the field of arts and humanities - Bedenlier, Svenja; Bond, Melissa; Buntins, Katja; Zawacki-Richter, Olaf; Kerres, Michael (Australasian Journal of Educational Technology, 2020)
Understanding how educational technology can enhance student engagement is becoming increasingly necessary in higher education, and particularly so in arts and humanities, given the communicative nature of courses. This narrative systematic review synthesises 42 peer-reviewed arts and humanities articles published between 2007-2016, indexed in four international databases. The results indicate that the majority of research has been undertaken in language learning, predominantly in East Asian countries, with limited grounding of research in theory. This review found that educational technology supports student engagement, with behavioural engagement by far the most prevalent dimension. Affective engagement was the lowest observed dimension, with affective disengagement the most prevalent negative dimension. Blogs, mobile learning, and assessment tools were the most effective at promoting engagement. However, caution and education in how to use technology are needed, as any use not underpinned by effective and informed pedagogy can also lead to students feeling overwhelmed and disengaging from learning. Further research is needed on online collaboration, as well as international courses that offer cross-cultural opportunities for language use, and the increased use of qualitative methods is also advise
Keywords: Educational technology; Arts and humanities; Student engagement; Language learning; Systematic review

Facilitating student engagement through educational technology: Towards a conceptual framework - Bond, Melissa; Bedenlier, Svenja (Journal of Interactive Media in Education, 2019)
The concept of student engagement has become somewhat of an enigma for educators and researchers, with ongoing discussions about its nature and complexity, and criticism about the depth and breadth of theorising and operationalisation within empirical research. This equally applies to research conducted in the field of educational technology and its application in schools and higher education. Recognising the inherent role that technology now plays in education, and the potential it has to engage students, this paper draws on a range of student engagement literature and conceptualises a provisional bioecological framework of student engagement that explicitly includes technology as one influential factor. This paper first proposes a definition of student engagement and provides an exploration of positive student engagement indicators. It then presents a bioecological framework, and the microsystemic facets of technology, teacher and curriculum are further explored in their relation to fostering student engagement. Based on this framework, implications for further theory-based research into student engagement and its relation to educational technology are discussed and recommendations for educators are give
Keywords: Educational technology; Bioecological model; K-12; Higher education; Theoretical framework; Student engagement

Faculty perceptions, awareness and use of open educational resources for teaching and learning in higher education: a cross-comparative analysis - Marin, Victoria; Zawacki-Richter, Olaf; Aydin, Cengiz H.; Bedenlier, Svenja; Bond, Melissa; Bozkurt, Aras; Conrad, Dianne; Jung, Insung; Kondakci, Yasar; Prinsloo, Paul; Roberts, Jennifer; Veletsianos, George; et al. (Research and Practice in Technology Enhanced Learning, 2022)
This paper explores faculty's perspectives and use of open educational resources (OER) and their repositories across different countries by conducting a multiple case study to find similarities and differences between academics' awareness, perceptions and use of OER, as well as examining related aspects of institutional policy and quality that may influence individual views. Data were collected through nine expert reports on each country studied (Australia, Canada, China, Germany, Japan, South Africa, South Korea, Spain and Turkey) and were analyzed through qualitative content analysis using thematic coding. Findings show the impact on individual OER adoption with regard to the individual control of diverse factors by faculty members; of institutional policies and quality measures on the externally determined factors (by the institution); and of institutional professional development and provision of incentives in more internally determined factors (by the faculty members themselves). These findings carry implications for higher education institutions around the world in their attempt to boost OER adoption by faculty members.
CRIS-Team WoS Importer:2022-04-08
Keywords: Open educational resources (OER); Repositories; Higher education (HE); Faculty members; International comparison

Female top performers in higher education STEM and humanities: socio-emotional perceptions and digital learning-related characteristics during COVID-19 - Ziegler, Albert; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kopp, Bärbel; Händel, Marion (Journal for the Education of Gifted Young Scientists, 2020)
In Germany, the 2020 summer semester was substantially influenced by the COVID-19 pandemic. In an empirical study, we focus on female top performing students in STEM and the humanities. Of particular interest was whether the measures associated with the pandemic constitute a risk-factor for a re-traditionalization of gender roles. Before lectures or courses began, students at a full-scale university were invited to participate in an online survey. We investigated four research questions: 1) Are women underrepresented in our sample among the top performers in STEM and the humanities? Are there gender differences among top performers with regard to (2) digital readiness, (3) socio-emotional and (4) learning related variables? The sample of the study consisted of 2,849 higher education STEM and humanities students. The study took place as an online survey. In the week before the start of the official lecture period, all students enrolled at the university were invited to take part via an e-mail correspondence from the Vice President of Education (survey access link). Participation in the survey took place via the Questback platform and was activated for 10 days. The cut-off point for the ability level was set at the 95th percentile of previous university achievements. To test Q1, we performed a hierarchical loglinear analysis with posthoc Chi² tests. In research questions Q2 - Q4 two-way ANOVAs were used to test the effects of gender and subject. Results indicate equal shares of female and male students among the top performers, with women overrepresented in the humanities and men overrepresented in STEM relative to their proportion of the student population. The analysis of socio-emotional and learning-related factors showed risk factors for high performing female students such as lower self-efficacy, but no major emotional vulnerability. Overall, the data suggest that at the beginning of the COVID-19 pandemic, female top performers had still been able to compensate for the risk factors.<br
Keywords: Gender; STEM; Humanities; Higher Education; High Ability; COVID-19; Digital Learning; Socio-emotional perceptions

“Generation invisible?“. Higher education students’ (non)use of webcams in synchronous online learning - Bedenlier, Svenja; Wunder, Iris; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (International Journal of Educational Research Open, 2021)
The pandemic situation continues to influence teaching and learning in higher education, with students oftentimes participating in synchronous videoconferencing sessions as a means to interact with peers and instructors. The frequently noted non-use of webcams by students incited the current study, investigating usage behavior as well as potentially related course variables and individual characteristics. N = 3,527 students from a German university took part in an online survey at the end of the regular summer term 2020 (August 2020). Findings indicate that students’ webcam usage behavior was related to personal thoughts and feelings (e.g., privacy), to course characteristics (e.g., group cohesion), and it differed due to specific groups (gender, study level). With the ongoing importance of videoconferencing in higher education, this study provides a foundation for further investigation into this synchronous learning context. <
Keywords: Webcam use; COVID-19 pandemic; Social presence; Individual differences

Helplessness among University Students: An Empirical Study Based on a Modified Framework of Implicit Personality Theories - Ziegler, Albert; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kopp, Bärbel; Händel, Marion (Education Sciences, 2021)
Due to the COVID-19 pandemic, and within a very short period of time, teaching in the 2020 summer term changed from predominantly on-site to online instruction. Students suddenly faced having to adapt their learning process to new demands for which they may have had both insufficient digital skills and a lack of learning resources. Such a situation carries the risk that a substantial number of students become helpless. The aim of our empirical study was to test a hybrid framework of helplessness that includes both objective causes of helplessness and students’ subjective interpretations of them. Before lectures or courses began, students of a full-scale university were invited to participate in an online survey. The final sample consists of 1690 students. Results indicate that objective factors as well as their subjective interpretations contributed to the formation of helplessnes
CRIS-Team Scopus Importer:2021-11-05
Keywords: higher education; digital learning; COVID-19 pandemic; helplessness; implicit theories of personality

Helplessness Among University Students: An Empirical Study Based on a Modified Framework of Implicit Personality Theories - Ziegler, Albert; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Händel, Marion (Journal of Science Education, 2021)
Due to the COVID-19 pandemic, and within a very short period of time, teaching in the 2020 summer term changed from predominantly on-site to online instruction. Students suddenly faced having to adapt their learning process to new demands for which they may have had both insufficient digital skills and a lack of learning resources. Such a situation carries the risk that a substantial number of students become helpless. The aim of our empirical study was to test a hybrid framework of helplessness that includes both objective causes of helplessness and students' subjective interpretations of them. Before lectures or courses began, students of a full-scale university were invited to participate in an online survey. The final sample consists of 1,690 students. Results indicate that objective factors as well as their subjective interpretations contribute to the formation of helplessnes

„I can do this – better than I thought. Instructors‘ experiences of the digital summer term 2020“. - Schmidt, Claudia; Bedenlier, Svenja (EDEN 11th Research Workshop., 2020)

Institutional Measures for Supporting OER in Higher Education: An International Case-Based Study - Marín, Victoria I.; Zawacki-Richter, Olaf; Aydin, Cengiz H.; Bedenlier, Svenja; Bond, Melissa; Bozkurt, Aras; Conrad, Dianne; Jung, Insung; ondakci, Yasar; Prinsloo, Paul; Roberts, Jennifer; Veletsianos, George; et al. (Open Education Studies, 2022)
Open Educational Resources (OER) in higher education cannot be put into practice without considering institutional contexts, which differ not only globally but also within the same country. Each institutional context provides educators with opportunities or limitations where Open Educational Practices (OEP) and OER for teaching and learning are involved. As part of a broader research project, and as a follow-up to national perspectives, an international comparison was conducted, based on institutional cases of nine different higher education systems (Australia, Canada, China, Germany, Japan, South Africa, South Korea, Spain, Turkey). Aspects regarding the availability of infrastructure and institutional policies for OER, as well as the existence of measures directed at OER quality assurance and at the promotion of the development and use of OER were covered. The resulting theoretical contribution sheds light on an international comparative view of OER and points towards country-specific trends, as well as differences among institutions. These aspects could provide an impetus for the development of institutional guidelines and measures. In line with international literature on the topic, recommendations are derived to promote/ enhance the use of OER in teaching and learning in higher education at the institutional level.
CRIS-Team Scopus Importer:2022-09-30
Keywords: faculty development; Higher education institutions; institutional policies; international case-based study; open educational resources (OER)

International Collaboration in the Field of Educational Research: A Delphi Study - Bond, Melissa; Marin, Victoria; Bedenlier, Svenja (Journal of New Approaches in Educational Research, 2021)
(International) research collaboration (IRC) is considered one of the most important aspects of academic careers and, although it is often linked to co-authorship, investigations of academic perceptions and practices are rare. Reflections on factors affecting IRC, as well as effective technology for use in IRC are also now particularly vital, due to the outbreak of COVID-19. The aim of this three-round Delphi study, conducted prior to the pandemic, was to explore why and how academics conduct IRC in the field of Education. The results indicate that the benefits of IRC are more relevant than the barriers, and that networking with and learning from others are two of the most important reasons for conducting IRC. Four stages of IRC were identified, alongside a range of influencing factors, which could inform future project management training. Suggestions for institutional IRC policy are provided, as well as considerations for early career researchers.
CRIS-Team Scopus Importer:2021-08-20
Keywords: DELPHI METHOD; EDUCATIONAL POLICY; EDUCATIONAL RESEARCH; INTERNATIONAL RESEARCH COLLABORATION

Internationalization of higher education and the impacts on academic faculty members - Bedenlier, Svenja; Zawacki-Richter, Olaf (Research in Comparative and International Education, 2015)
Research on internationalization processes in higher education has steadily increased over the past decades. However, there is still a lack of analysis of how these developments have affected higher education and, specifically, the group of academic faculty members. To close this gap, this study explores the effects of internationalization on this stakeholder group. A two-round mixed-methods approach was applied in order to identify impacts on this group and rate their importance. From the internationally composed expert panel’s responses, 25 impacts on the individual, institutional, and global level were derived, constituting a preliminary foundation for further research on this topic. Findings from the study indicate a need for further investigation of the nature of individual impacts, as well as discussion on the separation of globalization and internationalization in higher education. Furthermore, they demonstrate the necessity of conducting research differentiated according to higher education systems and the faculty members withi
Keywords: Globalization and international higher education; Academic faculty members; Two-round mixed-methods approach; Internationalization of higher education

Internationalization within higher education and its influence on faculty: experiences of Turkish academic staff - Bedenlier, Svenja (Journal of Research in International Education, 2017)
In this article, findings are reported from a phenomenology-oriented study on prolonged international mobility and the effects of internationalization on the professional lives of six academic faculty at a Turkish research university. Drawing on research on international mobility of faculty and the present context of Turkish higher education, this investigation identifies three distinct phases of the sojourn abroad – motivation to go abroad, being abroad, repatriating to Turkey – being framed by the supportive and demanding culture of the specific institution. For the participants, ambivalently perceived effects at the individual, institutional and national level include networks gained, the imperative to publish in English, and the lack of a comprehensive national policy for internationalizatio
Keywords: center and periphery; academic faculty; Turkey; Internationalization of higher education

Introduction to Global Perspectives and Internationalization in ODDE - Bedenlier, Svenja (SpringerPlus, 2022)
This introductory chapter delves into global perspectives and internationalization surrounding around the field of ODDE by distinguishing and exploring the concepts of global perspectives on ODDE and the globalization and internationalization within ODDE. This introduction outlines the setup of the section, connects the individual chapters, and develops the section per content areas covered. Following this portrayal, implications for ODDE theory, practice, and research in global perspective are then drawn from the contributions in this section. In sum, the chapters call for continuous engagement of researchers and practitioners in the field to facilitate a broad and multifaceted scientific discussion on the practice of ODDE that is mindful of the entanglement of culture, voice, policy, and economics in a global view.<br

Introduction to Global Perspectives and Internationalization in ODDE - Bedenlier, Svenja (Handbook of Open, Distance and Digital Education, 2023)
This introductory chapter delves into global perspectives and internationalization surrounding around the field of ODDE by distinguishing and exploring the concepts of global perspectives on ODDE and the globalization and internationalization within ODDE. This introduction outlines the setup of the section, connects the individual chapters, and develops the section per content areas covered. Following this portrayal, implications for ODDE theory, practice, and research in global perspective are then drawn from the contributions in this section. In sum, the chapters call for continuous engagement of researchers and practitioners in the field to facilitate a broad and multifaceted scientific discussion on the practice of ODDE that is mindful of the entanglement of culture, voice, policy, and economics in a global view.
CRIS-Team Scopus Importer:2024-02-14
Keywords: Global perspectives; Internationalization; ODDE

Invisible borders in educational technology research? A comparative analysis - Marín, Victoria I.; Buntins, Katja; Bedenlier, Svenja; Bond, Melissa (Educational Technology Research and Development, 2023)
Educational research is reflective of the nature and structure of national and regional education systems and their historical evolution. Educational technology research, as an area within educational research, reflects this case particularly prominently. Although individual countries and regions have varying research traditions, the publication of research in English as the scientific lingua franca can lead to missing nuances in terminology, which is often not reflected upon. Despite this, the exploration of research from different countries can still uncover diverse topical clusters. This study aims to identify the research topics in educational technology research in three countries (Germany, Spain and the United Kingdom), each with their own research traditions, through the terms used. To this end, a bibliometric analysis of 3034 article abstracts and keywords from 29 English-language Web of Science journals in the field of education and educational research was conducted, with a focus on educational technology. In addition, the quantitative findings are comparatively analysed by considering the corresponding cultural clusters. Main findings include diverse research foci in the three countries, also showing that distinct research traditions are still present, despite using English as lingua franca. Therefore, research articles written in English by non-English authors often do not reflect the same meanings in each country, despite using the same words. The conclusions reflect upon the need to establish ways of understanding the traditions behind those research articles and build collaborative systems to illustrate nuances in this research.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Bibliometric analysis; Comparative research; Educational research traditions; Educational technology research

Learning by doing? Practical reflections on conducting a systematic review in educational technology research - Bedenlier, Svenja; Bond, Melissa; Buntins, Katja; Zawacki-Richter, Olaf; Kerres, Michael; et al. (Systematic Reviews in Educational Research. Methodology, Perspectives and Application, 2019)
Drawing on an example of a large systematic review that was conducted on the use of educational technology and student engagement in higher education, we provide practical insights into how we proceeded throughout the review phases. Readers and researchers embarking on a systematic review themselves might find the contents of this chapter useful, in order to better prepare themselves for issues that can arise when undertaking such an endeavour.<br
Keywords: Systematic Reviews; Educational Research; Practical Examples for Systematic Reviews; Student Engagement; Educational Technology; Academic Success; Education Research; Open Access

Mapping research in student engagement and educational technology in higher education: a systematic evidence map - Bond, Melissa; Buntins, Katja; Bedenlier, Svenja; Zawacki-Richter, Olaf; Kerres, Michael (International Journal of Educational Technology in Higher Education, 2020)
Digital technology has become a central aspect of higher education, inherently affecting all aspects of the student experience. It has also been linked to an increase in behavioural, affective and cognitive student engagement, the facilitation of which is a central concern of educators. In order to delineate the complex nexus of technology and student engagement, this article systematically maps research from 243 studies published between 2007 and 2016. Research within the corpus was predominantly undertaken within the United States and the United Kingdom, with only limited research undertaken in the Global South, and largely focused on the fields of Arts & Humanities, Education, and Natural Sciences, Mathematics & Statistics. Studies most often used quantitative methods, followed by mixed methods, with little qualitative research methods employed. Few studies provided a definition of student engagement, and less than half were guided by a theoretical framework. The courses investigated used blended learning and text-based tools (e.g. discussion forums) most often, with undergraduate students as the primary target group. Stemming from the use of educational technology, behavioural engagement was by far the most often identified dimension, followed by affective and cognitive engagement. This mapping article provides the grounds for further exploration into discipline-specific use of technology to foster student engagement.
Keywords: Educational technology; Higher education; Systematic review; Evidence map; Student engagement

Online Learning - Blaschke, Lisa Marie; Bedenlier, Svenja (2020)
With the ubiquity of the Internet and the pedagogical opportunities that digital media afford for education on all levels, online learning constitutes a form of education that accommodates learners' individual needs beyond traditional face-to-face instruction, allowing it to occur with the student physically separated from the instructor. Online learning and distance education have entered into the mainstream of educational provision at of most of the 21st century's higher education institutions. With its consequent focus on the learner and elements of course accessibility and flexibility and learner collaboration, online learning renegotiates the meaning of teaching and learning, positioning students at the heart of the process and requiring new competencies for successful online learners as well as instructors. New teaching and learning strategies, support structures, and services are being developed and implemented and often require system-wide changes within higher education institutions. Drawing on central elements from the field of distance education, both in practice and in its theoretical foundations, online learning makes use of new affordances of a variety of information and communication technologies-ranging from multimedia learning objects to social and collaborative media and entire virtual learning environments. Fundamental learning theories are being revisited and discussed in the context of online learning, leaving room for their further development and application in the digital ag

Preservice Teachers' Online Self-Regulated Learning: Does Digital Readiness Matter? - Fuchs, Katharina; Pösse, Lisa; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Education Sciences, 2022)
(1) Background: Teaching in today's schools asks teachers to foster self-regulated learning and digital competences in children and young people. In order to do so, teachers first need to acquire and use these competences themselves. (2) Methods: Based on a mixed-methods approach, the study investigates self-regulated learning in online courses of N = 129 preservice teachers at a German university. (3) Results and conclusions: Perceiving their digital readiness as generally high, preservice teachers appear to not overly self-regulate their learning in the online environment. Finally, preservice teachers' digital readiness was related only weakly to their online self-regulated learning. A discussion is offered which shows teacher education as a broader phenomenon and implies the need for professional development for teacher educators. Additionally, it is argued to link research on self-regulated learning more closely to research on online learning environments in teacher education.
CRIS-Team WoS Importer:2022-05-06

Self-Regulated Resource Management in Emergency Remote Higher Education – Status Quo and Predictors - Naujoks, Nick; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf Josef; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Frontiers in Psychology, 2021)
Because of the COVID-19 pandemic in the spring term 2020, students faced a sudden change from on-campus learning to online learning with synchronous and asynchronous online courses (emergency remote teaching). To study successfully, students not only needed to be prepared in terms of digital readiness (workspace, IT equipment, previous online learning experiences, and sharing information online), they also faced challenges that pertained to the self-regulated management of external resources (environment structuring, time management, and help-seeking). In the current study, we investigated students’ digital readiness for the sudden switch to online learning; differences between students’ intended and actual use of external resource management strategies; and the influence of students’ digital readiness on their actual use of resource management strategies. Students enrolled in a full-scale, German university (N = 662) answered two online questionnaires (before and in the middle of the term). Descriptive statistics indicated that students seemed to be ready to study online. However, a repeated measures analysis of variance showed that students were not able to manage their resources during the term as frequently as intended. Finally, separate regression analyses revealed that availability of workspace and IT equipment predicted the use of environment structuring strategies. Additionally, IT equipment and information sharing behavior predicted students’ help-seeking. Based on the current results, we discuss implications for the promotion of student self-regulated learning in online emergency remote teaching based on both external resources and digital readiness.

Social network analysis of international student mobility: uncovering the rise of regional hubs - Kondakci, Yasar; Bedenlier, Svenja; Zawacki-Richter, Olaf (Higher Education, 2018)
Research on the patterns of international student mobility and the dynamics shaping these patterns has been dominated by studies reflecting a Western orientation, discourse, and understanding. Considering political, economic, cultural, historical, and ecological factors, this study argues that international student mobility is not only an issue of the economically developed, politically stable, and academically advanced Western world but also one that involves countries with different economic, political, and academic characteristics. Taking into account various theoretical orientations, this study argues that political, economic, cultural, and historical factors have led to the emergence of non-traditional destinations for international students; these countries are labeled as emergent regional hubs. In order to empirically test this, a social network analysis was conducted on a worldwide dataset representing 229 countries. The findings evidenced the strong position of traditional destinations for international students. However, the results also suggest the rise of several regional hubs, which are undergoing internationalization processes in different forms and with different rationales. The mobility patterns in emerging regional hubs deviate from those in traditional destinations, which fundamentally change the nature of internationalization in this context.
Keywords: International student mobility; Regional hubs; Social network analysis

Stress development during emergency remote teaching in higher education - Obermeier, Ramona; Gläser-Zikuda, Michaela; Bedenlier, Svenja; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Learning and Individual Differences, 2022)
Higher education includes e-learning in addition to on-site learning. Still, the shift to Emergency Remote Teaching (ERT) as reaction to the Covid-19 pandemic in the summer semester 2020, presented a challenging situation for students. Cross-sectional studies pointed towards higher stress levels of students. However, only a few studies addressed the development of students' stress across several dimensions (joy, worry, tension, demands) within one semester. The current study analyzed trajectories of stress in ERT in relation to age, gender, digital readiness, and experience of loneliness, based on a sample of N = 2795 German students. Latent Growth Curve Models (LGCM) revealed a significant increase in demands, tension and worries and a decrease in joy during the summer term 2020. The development of tension and demands was influenced by age, gender, digital readiness, and loneliness. The decrease in joy and increase in worries could be primarily attributed to digital readiness and loneliness.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Digital readiness; Emergency remote teaching; Higher education; Perceived stress; Social embeddedness

Systematic Reviews in Educational Research. Methodology, Perspectives and Application - Zawacki-Richter, Olaf; Kerres, Michael; Bedenlier, Svenja; Buntins, Katja; Bond, Melissa; et al. (Springer VS, 2020)
In this open access edited volume, international researchers of the field describe and discuss the systematic review method in its application to research in education. Alongside fundamental methodical considerations, reflections and practice examples are included and provide an introduction and overview on systematic reviews in education researc
Keywords: systematic reviews; education science

Teaching Trends 2016: Digitalisierung in der Hochschule: mehr Vielfalt in der Lehre - Pfau, Wolfgang; Baetge, Caroline; Bedenlier, Svenja; Kramer, Carina; Stöter, Joachim (Waxmann, 2016)
Keywords: 2016; Clausthal <2016>; Clausthal-Zellerfeld; e-learning; Hochschule; Konferenzschrift; Kongress; Lehre; Lerntechnik; Unterrichtsmethode; Virtuelle Hochschule

The Development of Distance Education Systems in Turkey, the Russian Federation and Saudi Arabia - Bedenlier, Svenja; Zawacki-Richter, Olaf; Kondakci, Yasar; Alturki, Utman; Aldraiweesh, A; Püplychhuysen, Diana (European Journal of Open, Distance and e-Learning, 2015)
In many countries, open and distance education is perceived as a way to meet the growing need for higher education. This paper explores the development of online and distance education in three countries that are still a white spot on the landscape of international distance education research although they have implemented elaborated distance education systems: Turkey, Russia and Saudi-Arabia. In order to understand the current state of distance education systems in the three countries, their respective systems are described from a historical perspective, compared in regard to their organization, important institutions for open and distance education and current developments. This comparative analysis directs the focus on little investigated education systems and contributes to an enhanced understanding of their past, present, and future.<br
Keywords: distance education; open education

The Digital Turn in Internationalization. Konzepte, Strategien und Praktiken. - Bedenlier, Svenja; Bruhn-Zaß, Elisa (2021)
Virtuelle Mobilität, MOOCs, Blended Mobility, Erasmus without Papers, OER oder vollständig online angebotene Studienangebote – dies sind nur Ausschnitte, in denen sich die beiden Querschnittsthemen Internationalisierung und Digitalisierung verbinden und in hochschulische Praxis Eingang finden.Die Digitalisierung neue Potenziale für eine umfassende Internationalisierung von Hochschulen, beispielsweise in der Lehre, in der Unterstützung von physischer Mobilität oder in der Gestaltung von Partnerschaften. Die zwölf Beiträge in diesem Themenheft adressieren verschiedene Facetten dieses Themas und richten den Blick vor allem auf die Gestaltung digitaler internationaler Lehr-Lernszenarien in der Hochschulbildung.<br
Keywords: Internationalisierung; Digitalisierung; Hochschule

‘The Impact of my Work would be Greater here than there’: Implications of the International Mobility of Colombian Academics - Bedenlier, Svenja (Research in Comparative and International Education, 2018)
Internationalization of higher education affects academic faculty in various ways. However, the internationalization experience of faculty in Latin America, a region concerned with internationalization only quite recently, has not yet been sufficiently researched. This research gap is addressed with this qualitative interview study. Five Colombian academics relate their experiences of internationalization, with a key focus on their own international mobility and the effects this has had on their professional lives and their institutional environment. Qualitative content analysis resulted in the identification of the four wider themes of mobility as personal professional enrichment, the ability to make an impact within Colombian higher education and, on the institutional level, to engage with the concept of internationalization at home and revisiting the role of academics in advancing internationalization. These themes are discussed against the background of literature on faculty mobility and the specific situation of emerging countrie
Keywords: faculty; Colombia; internationalization of higher education; international mobility

The Structure of Social Networks and Its Link to Higher Education Students’ Socio-Emotional Loneliness During COVID-19 - Hopp, Manuel; Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Frontiers in Psychology, 2022)
Lonely students typically underperform academically. According to several studies, the COVID-19 pandemic is an important risk factor for increases in loneliness, as the contact restrictions and the switch to mainly online classes potentially burden the students. The previously familiar academic environment (campus), as well as the exchange with peers and lecturers on site, were no longer made available. In our cross-sectional study, we examine factors that could potentially counteract the development of higher education student loneliness during the COVID-19 pandemic from a social network perspective. During the semester, N = 283 students from across all institutional faculties of a German comprehensive university took part in an online survey. We surveyed their social and emotional experiences of loneliness, their self-reported digital information-sharing behavior, and their current egocentric networks. Here, we distinguished between close online contacts (i.e., mainly online exchanges) and close offline contacts (i.e., mainly in-person face-to-face exchanges). In addition, we derived the interconnectedness (i.e., the densities of the egocentric networks) and heterogeneity (operationalized with the entropy) of students’ contacts. To obtain the latter, we used a novel two-step method combining t-distributed stochastic neighbor embedding (t-SNE) and cluster analysis. We explored the associations of the aforementioned predictors (i.e., information-sharing behavior, number of online and offline contacts, as well as interconnectedness and heterogeneity of the close contacts network) on social and emotional loneliness separately using two hierarchical multiple linear regression models. Our results suggest that social loneliness is strongly related to digital information-sharing behavior and the network structure of close contacts. In particular, high information-sharing behavior, high number of close contacts (whether offline or online), a highly interconnected network, and a homogeneous structure of close contacts were associated with low social loneliness. Emotional loneliness, on the other hand, was mainly related to network homogeneity, in the sense that students with homogeneous close contacts networks experienced low emotional loneliness. Overall, our study highlights the central role of students’ close social network on feelings of loneliness in the context of COVID-19 restrictions. Limitations and implications are discussed.
CRIS-Team Scopus Importer:2022-02-11
Keywords: COVID-19 pandemic; digital information-sharing behavior; interconnectedness; loneliness; network density; network heterogeneity; network homogeneity; social network

The webcam and student engagement in synchronous online learning: visually or verbally? - Händel, Marion; Bedenlier, Svenja; Kopp, Bärbel; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Ziegler, Albert (Education and Information Technologies, 2022)

Turkey - Kondakci, Yasar; Bedenlier, Svenja; Aydin, Cengiz Hakan (Open and Distance Education in Asia, Africa and the Middle East: National Perspectives in a Digital Age., 2019)

Two Decades of Research Into the Internationalization of Higher Education: Major Themes in the Journal of Studies in International Education (1997-2016) - Bedenlier, Svenja; Kondakci, Yasar; Zawacki-Richter, Olaf (Journal of Studies in International Education, 2018)
In recent decades, internationalization within higher education has emerged as a distinct field for practice and research. However, there are few meta-analyses of how the research trends and foci of this topic have evolved and shifted over time. This article analyzes the content of the Journal of Studies in International Education (JSIE), a central outlet for internationalization research, thus shedding light on overarching developments and trends within the field. In this investigation, the text-mining tool Leximancer is used to generate concept maps based on the titles and abstracts of all 406 scientific articles published in the JSIE between 1997 and 2016 (first issue). Four major developmental waves in this research area are revealed: delineation of the field (1997-2001), institutionalization and management of internationalization (2002-2006), consequences of internationalization: student needs and support structures (2007-2011), and currently, moving from the institutional to the transnational context of internationalization (2012-2016). The results show how the meaning of the concept has evolved to encapsulate several other related concepts in research on higher education, while reporting practices toward internationalization at individual, institutional, and national levels.
Keywords: internationalization of higher education; content analysis; research trends; Journal of Studies in International Education; research themes

Who cites whom? U.S.-American authored research syntheses in the field of educational technology: a bibliometric analysis - Buntins, Katja; Bedenlier, Svenja; Zawacki-Richter, Olaf (Learning Media and Technology, 2025)
Research syntheses are an important approach to capture and synthesize empirical studies in educational technology. However, despite their proclaimed impartial summary of available research, imbalances exist as to whose research is included due to publication language or in regard to the visibility of entire scientific communities. Using the concepts of academic hegemony and WEIRD research, a bibliometric analysis is conducted in order to explore how research syntheses of authors located in one of the so-called academic core countries–the U.S.A.–are positioned in international comparison, and how this potentially shapes the discourse on educational technology. For the bibliometric analysis, a corpus with N = 446 research syntheses is considered, comprised of 95 U.S.-authored and 351 non-U.S.-authored syntheses. Findings reveal that U.S.-authored syntheses are relatively self-referential and also draw heavily on databases of U.S.-based professional societies in their literature search. Over half of the syntheses cite other U.S.-based research, followed by Chilean, British, Canadian, Australian and German research. In contrast, U.S.-authored syntheses are cited globally, accentuating their perceived importance and influence. Findings point to the need to consider underlying influences and contextual factors for research syntheses in educational technology, reflect on citation practices and generalizability of findings from educational research.
CRIS-Team Scopus Importer:2025-05-23
Keywords: academic hegemony; bibliometric analysis; educational technology; generalizability; Research synthesis

Wie gestresst sind Lehramtsstudierende im Kontext der Umstellung auf digitale Lehre? - Obermeier, Ramona; Gläser-Zikuda, Michaela; Bedenlier, Svenja; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Lehrerbildung auf dem Prüfstand, 2021)

Wie gestresst sind Lehramtsstudierende im Kontext der Umstellung auf digitale Lehre? - Obermeier, Ramona; Gläser-Zikuda, Michaela; Bedenlier, Svenja; Kopp, Bärbel; Kammerl, Rudolf; Ziegler, Albert; Händel, Marion (Lehrerbildung auf dem Prüfstand, 2021)
Bedingt durch die Covid-19-Pandemie wurde das Sommersemester 2020 deutschlandweit als reines Digital-Semester aufbereitet. Dies stellte Hochschulen, Lehrende und Studierende vor große Herausforderungen. Lehramtsstudierende, die der Nutzung digitaler Medien tendenziell eher skeptisch gegenüberstehen, sich studienbedingt aber mit (medien)-didaktischen und -pädagogischen Fragen beschäftigen, stellen dabei eine Zielgruppe von besonderem Forschungsinteresse dar. Die vorliegende Studie thematisiert das Stresserleben von Lehramtsstudierenden im Zuge der Umstellung auf digitalisierte Lehre im Sommersemester 2020. Dabei werden unterschiedliche Voraussetzungen auf Studierendenseite (z. B. Medienkompetenz) und durch die Umstellung auf digitale Lehrangebote bedingte Faktoren, wie eine geringere soziale Eingebundenheit, berücksichtigt. Die Ergebnisse längsschnittlich erfasster Daten von N = 51 Studierenden des Grund- und Mittelschullehramts einer Hochschule zeigen eine Zunahme im Stresserleben im Digital-Semester. Die Befunde unterstreichen ferner die Bedeutung der erlebten sozialen Eingebundenheit für diese Entwicklung. Wenngleich die Studie aufgrund ihrer geringen Stichprobengröße eingeschränkt ist, liefert sie wichtige Erkenntnisse in der speziellen Situation der ad-hoc Umstellung der Hochschullehre, die auch für weitere Digitalisierungsprozesse des Lehramtsstudiums genutzt werden könne
Keywords: E-Learning; Lehrerbildung; Medienkompetenz; soziale Eingebundenheit; Stresserleben

Zur Rolle und Bedeutung von digitalen Medien in Internationalisierungsstrategien deutscher Hochschulen - Zawacki-Richter, Olaf; Bedenlier, Svenja (2015)